The elevation of higher learning - Zaini Ujang Dato' 1965- (Penerbit Universiti Teknologi Malaysia, 2009)
The Elevation of Higher Learning is a compilation of one writer's views on higher education, a sector which has swiftly become prominent in the public eye in echancing the appreciation of knowledge and improving its quality, especially among students and graduates. It is a frequently raised issue as universities have long been synonymous with the advancement of knowledge, its civilisation and traditions. This book answers several revevant questions such as: does the existence of hundreds of IPTs correspond to a better understanding of knowledge among Malaysians? Does the significance of knowledge and role of intellectuals garner more exposure in the scheme of national development? With the increasing number and influence of educated citizens, are the values of knowledge nurtured by sincere, noble habits becoming more apparent in society? This book is essential reading for policy makers, those involved in university management, administrators, researchers, academicians and intellectuals, lovers of knowledge, students and potential graduates. It is also suitable for researchers in research centres, companies and anyone who has an interest in intellectual issues and the matter of Higher Education.